The Evolving Journey of Green Hydrogen in India’s Progress Towards Net-Zero Carbon Emissions - Madhao Laud, Shivprasad (Digital Repository of Theses, 2026)
India is seeking a net-zero future, and Green Hydrogen (GH2) has become one of the strategic pillars of decarbonising energy and industrial systems. Still, various systemic obstacles such as a lack of adoption preparedness, unclear policy effects, the infrastructural and investment gap, safety risks, and scalability issues remain a challenge to its mass adoption. The objective of the research is to evaluate the effect of Government policies, organisational preparedness, infrastructure facilitation, risk perception, scalability plans, and safety interventions in determining the evolving role and future of GH2 in India. A mixed-methods research design was employed. Data collection involved both structured surveys and interviews with respondents from Government authorities and Private organisations. In addition, a content analysis was performed on companies operating within the Green Hydrogen (GH2) sector. This mixed-methods approach enabled a comprehensive understanding of the subject matter. Quantitative data were analysed using SPSS, employing Spearman’s correlation and logistic regression to explore relationships and predictive effects, while qualitative interview data were examined through thematic analysis. Findings show that Government Policy effectiveness, clarity, and incentives had no statistically significant impact on adoption readiness (p > 0.05). However, technological readiness (r = 0.435, p = 0.002), financial readiness (r = 0.542, p < 0.001), and workforce readiness (r = 0.467, p = 0.001) were positively associated with industry collaboration. Financial support mechanisms significantly reduced risk perception (r = 0.311, p = 0.028), although infrastructure availability did not. Scalability showed strong associations with hydrogen storage capacity (r = 0.633, p < 0.001) and Government-Private Sector collaboration (r = 0.659, p < 0.001). Safety training showed significant predictive power in reducing safety incidents (Estimate = 0.811, p = 0.019), exceeding that of regulatory compliance alone. Finally, the analysis suggests that a multi-pronged approach that includes investing in safety training, developing more storage infrastructure, increasing industry-policy alignment, and engaging more stakeholders is necessary. The results provide policymakers and industry leaders with guidelines that they can use to create a GH2 ecosystem in India that is safer, scalable, and investor-friendly.